Workload and Labor Predictors of Overtime Hours (An Empirical Study on Dataset) - Tekin Akgeyik (Sosyal Siyaset Konferansları Dergisi)
According to Turkish Labor Code 4857, overtime is extra working hours that exceed 45 hours per week. It is a method of increasing production through a greater usage of human capital (Jirjahn, 2008). However, excessive work hours may negatively affect workers’ physical and mental wellbeing. Consequently, the International Labor Organization and European Union place restrictions on working hours. This paper seeks to find the workload and labor predictors of the hours from overtime using data from an aluminum company, Tekirdag. The sample period covers team-level data from January 2012 to December 2016. The study included company data on ten production teams working in four units: preparation (casting and molding teams), processing (powder coating, extrusion, and anodizing teams), finishing (wood effect coating, thermal break, and machining teams), and distribution (packaging and shipping teams). The data originate from the departments of production planning and of personnel. The hierarchical regression model of all the samples demonstrated that the volume of production as workload factor was the main determinant of overtime work hours, accounting for 45.6%. Additionally, employee factors such as the hours of sick leave, annual paid leave, and other leaves were found as predictors of overtime hours worked. All these variables explained 53.6% of the variance in the dependent variable. Secondly, the analysis of the sub-groups suggested that workload volume was a significant determinant of overtime hours worked for the processing, finishing, and distribution teams.